Trojan malware analysis using reverse engineering method in Windows 7 - Riyana, Ade; Santoso, Banu; Hartono, Rudi (Technium Social Sciences Journal, 2022)
Incidence response of malware attack or malware attack. Security attacks have now undergone many developments, which were originally individuals (hackers) now becoming more widespread (cyberwars). It is possible for someone to be attacked by malware on the computer system used. Malware can attack through offline or online media such as sms, chat or spam (whatsapp, instagram, email, telegram). Many think that malware can be easily handled with just an antivirus. Malware has its own defense system and can hide itself from an antivirus or even infect it. Malware can be handled by knowing how to work when attacking a computer system. Malware analysis is carried out by implementing trojan and bot malware on laptops and computers using reverse engineering methods. The downloaded application turns out to be a trojan in disguise, to find out whether the application is indeed infected with malware, it is necessary to analyze it firstr. This research will analyze the Danabot application that is infected with trojan malware by reverse engineering method. To check the authenticity of malware, it is necessary to check for md5 and sha256 malware, which means that the downloaded Danabot application has been infected with trojan malware, not a corrupt or damaged application.